Everyone brave is forgiven - Cleave, Chris (Simon & Schuster, 2016)
Set in London during the years of 1939-1942, when citizens had slim hope of survival, much less victory; and on the strategic island of Malta, which was daily devastated by the Axis barrage, Everyone Brave is Forgiven features little-known history and a perfect wartime love story inspired by the real-life love letters between Chris Cleave's grandparents. This dazzling novel dares us to understand that, against the great theater of world events, it is the intimate losses, the small battles, the daily human triumphs that change us most.